The Relationship Between Family Support and Self-Confidence in Managing Chronic Kidney Failure Patients in the Hemodialysis - Elva Syaharani; Juliati Koesrini; Dian Pitaloka Priasmoro (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Background: Chronic Kidney Disease (CKD) is a progressive disease that requires patients to undergo long-term hemodialysis. This process places various physical and psychological demands on patients, requiring them to consistently manage their self-care. Self-efficacy is a crucial factor that influences patients’ confidence in undergoing therapy, while family support plays a significant role in helping patients maintain motivation and compliance during treatment. However, patients' self-efficacy may be impacted by the varying degrees of family support they receive. Purpose: Understanding the connection between self-efficacy and family support in hemodialysis patients with chronic kidney disease(CKD). Methods: Her research employed a cross-sectional methodology and a correlational quantitative design. Using basic random sampling, 102 patients made up the sample. Family support and self-efficacy questionnaires were used to gather data, and the Spearman Rank test was used for analysis with a significance level of α = 0.05. Results: Most respondents showed great self-efficacy (91.2%) and strong familial support (91.2%). Family support and self-efficacy were strongly and significantly correlated (r = 0.612; p = 0.000). Conclusion: The degree of self-efficacy of CKD patients receiving hemodialysis is strongly correlated with family support. Optimal Family Support can increase patients’ confidence and ability to manage their care.